Long-term changes in corneal densitometry and associated factors following small incision lenticule extraction for moderate and high myopia - Xu, Changqin; Yang, Dongmei; Zhao, Wuxiao; Long, Zhigang; Zhang, Zhe; Shen, Yang; Zhou, Xingtao; Zhao, Jing (Frontiers in Medicine, 2022)
Purpose: To investigate long-term trends in corneal densitometry and associated influencing factors following small incision lenticule extraction (SMILE). Methods: A comparative study was performed among 72 eyes of 38 patients undergoing SMILE. Eyes were divided into moderate myopia (mean spherical equivalent [SE], -4.22 ± 0.68D) and high myopia (mean SE, -7.63 ± 1.09 D) groups. Visual acuity, manifest refraction, corneal topography and corneal densitometry (CD) were evaluated preoperatively and three years postoperatively. Results: The efficacy indices at last postoperative follow-up (42.47±0.51 months) were 0.92±0.21 and 0.97±0.22, the safety indices were 1.12±0.17 and 1.14±0.21 for high and moderate myopia, respectively (all P>0.05). CD values in the 0–6 mm zone of the posterior corneal layer were statistically significantly lower than the preoperative values in both groups. Postoperative CD values (0–2 mm zone) in the posterior layer of the high myopia group were statistically significantly lower than in the moderate myopia group (P=0.025); CD values (2–6 mm zone) in the anterior layer were higher in the high myopia group (P=0.026). Correlation analyses showed that CD values in the 0–2 mm middle layer were negatively correlated with lenticule thickness in high myopia (r=-0.411, P=0.016); there was a negative correlation between the CD values (0–6 mm) and corneal oblique trefoil in this group (P<0.05). Conclusion: Corneal transparency in the 0–6 mm zone of the posterior cornea increased following SMILE in moderate and high myopia. Long-term corneal transparency in high myopia may be correlated with oblique trefoil and lenticule thickness.